Pelatihan Tahsin Dan Makhorijul Huruf Surah Al-Fatihah Untuk Meningkatkan Kualitas Bacaan Al-Qur’an - Albab, Fikri Ulul; Lestari, Sadiyah Dwiyani; Rahmadani, Eka; Juliansyah, Reza; Nurlatipah, Siska; Elpiana, Eva (-, 2026)
Teaching and learning activities at MDTA Baitul Mukhlisin have been running effectively with a predetermined schedule from Monday to Friday, including reciting the Koran, writing, memorizing short letters, memorizing prayers and others. However, there are still many shortcomings and obstacles that are experienced so that they become obstacles faced. Among the obstacles found are the lack of parental attention to the development of students' recitation, the lack of innovative learning media, teachers who are less competent, and the habit of students in learning or reading the Koran not using tajwid and makhorijul letters in depth so that when reading the holy verses there are still mistakes in reading. So, in this case, there needs to be follow-up and special treatment to improve and read in the future so that no mistakes are found. Supporting facilities also greatly affect the sustainability of learning. Learning media with the development of the era can also be used as an intermediary in learning, for example animated videos, tajwid training in the form of videos and many more. This research was conducted to improve and enhance the quality of reading the Qur'an.